Prediction cost maintenance model of office building based on condition-based maintenance - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Polish Maintenance Society, 2014)
Building maintenance costs are continuously increasing as a result of poor maintenance. Consequently, there is an urgent need to develop solutions to reduce the maintenance costs. Various studies demonstrated that the characteristics of condition-based maintenance are directly related to the cost performance. Thus, this paper seeks to establish the relationships between the characteristics of condition-based maintenance and the cost performance. The researcher then developed a regression model for maintenance planning and prediction. The study adopted a mix method approach that includes questionnaire survey, interview, and case study. The findings highlighted the reliability of maintenance data and information as the most significant characteristic of condition-based maintenance. Consequently, the study concluded that the planning and the application of the condition-based maintenance strategy should consider its significant characteristics and make reference to the resulting prediction model. Furthermore, the study recommended measures to improve the significant characteristics and the cost performance in practice.